Synthesis, Characterisation and Mechanism of Action of Anticancer 3-Fluoroazetidin-2-ones - Azizah M. Malebari; Gabriela Duffy Morales; Brendan Twamley; Darren Fayne; Mohemmed Faraz Khan; Eavan C. McLoughlin; Niamh M. O'Boyle; Daniela M. Zisterer; Mary J. Meegan (MDPI AG, 2022)
The stilbene combretastatin A-4 (CA-4) is a potent microtubule-disrupting agent interacting at the colchicine-binding site of tubulin. In the present work, the synthesis, characterisation and mechanism of action of a series of 3-fluoro and 3,3-difluoro substituted β-lactams as analogues of the tubulin-targeting agent CA-4 are described. The synthesis was achieved by a convenient microwave-assisted Reformatsky reaction and is the first report of 3-fluoro and 3,3-difluoro β-lactams as CA-4 analogues. The β-lactam compounds 3-fluoro-4-(3-hydroxy-4-methoxyphenyl)-1-(3,4,5-trimethoxy phenyl)azetidin-2-one 32 and 3-fluoro-4-(3-fluoro-4-methoxyphenyl)-1-(3,4,5-trimethoxyphenyl)azetidin-2-one) 33 exhibited potent activity in MCF-7 human breast cancer cells with IC50 values of 0.075 µM and 0.095 µM, respectively, and demonstrated low toxicity in non-cancerous cells. Compound 32 also demonstrated significant antiproliferative activity at nanomolar concentrations in the triple-negative breast cancer cell line Hs578T (IC50 0.033 μM), together with potency in the invasive isogenic subclone Hs578Ts(i)8 (IC50 = 0.065 μM), while 33 was also effective in MDA-MB-231 cells (IC50 0.620 μM). Mechanistic studies demonstrated that 33 inhibited tubulin polymerisation, induced apoptosis in MCF-7 cells, and induced a downregulation in the expression of anti-apoptotic Bcl2 and survivin with corresponding upregulation in the expression of pro-apoptotic Bax. In silico studies indicated the interaction of the compounds with the colchicine-binding site, demonstrating the potential for further developing novel cancer therapeutics as microtubule-targeting agents.